Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 4 Quadratic Functions and Factoring - 4.4 Solve ax(squared) + bx + c = 0 by Factoring - 4.4 Exercises - Quiz for Lessons 4-1-4.4 - Page 265: 5



Work Step by Step

We use the FOIL method. Then we simplify until the equation is in the form $y=ax ^2+bx+c$. Hence: $g(x)=-2(x+3)(x-7)=-2(x^2-7x+3x-21)=-2(x^2-4x-21)=-2x^2+8x+42$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.